2000
DOI: 10.1243/1350650001543458
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surface defects on the fatigue of water-and oil-lubricated contacts

Abstract: A study into effects of surface defects on rolling contact fatigue of brass and rail steel has been undertaken on a twin-disc rolling-sliding test machine with both oil and water lubrication. Furrows and dents were artificially introduced into the disc surfaces, and surface micro cracks and pits were monitored by means of surface replication. The results showed that artificial dents only reduce the fatigue life of the contact with oil, but not water lubrication. With oil lubrication the fatigue failure initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Table 2 shows some of the mechanical properties of the tested ADIs, referred by the corresponding austempering isothermal transformation temperature. The letter D stands for "Double-step" treatments, a nonconventional austempering sequence that includes a short martensitic stage [15]. Table 2 Mechanical properties of tested ADIs …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows some of the mechanical properties of the tested ADIs, referred by the corresponding austempering isothermal transformation temperature. The letter D stands for "Double-step" treatments, a nonconventional austempering sequence that includes a short martensitic stage [15]. Table 2 Mechanical properties of tested ADIs …”
Section: Methodsmentioning
confidence: 99%
“…Several indentation techniques have already been used by different authors [1][2][3][4][15][16][17], sometimes producing large surface defects (usually machining or electro-erosion furrows), some other times creating small surface defects of typical shape, namely spherical, conical and pyramidal indentations. For this work two important conditions had to be considered: indentations should not modify global contact conditions (surface failure should not be caused by the presence of the indentations) and local damaging of austempered ductile iron surfaces should occur after a relatively short period of time.…”
Section: Indentationsmentioning
confidence: 99%
“…Referring to his results, water absorbing capacity of oil varies according to chemical composition and additives of the oil. Gao et al [42] reported that presence of water changes the mechanism of rolling contact fatigue failure from spall-related failure into crack-related failure. Schatzberg and Felsen [37,38] have concluded that increasing water content from less than 10ppm to 100ppm in lubricant causes 43 percent reduction in fatigue life at 9 GPa stress level.…”
Section: The Effect Of Water Contamination On Hydrogen Permeationmentioning
confidence: 99%
“…Surface cracks could originate from these defects at lower stresses and propagate until material failure. Gao et al [42] have revealed that cracks are formed more readily and in greater numbers in waterlubricated contacts compared to oil-lubricated contacts. Secondly, once cracks have formed, water could squeeze into the crack by the passing load and forced ahead of the surface microcrack.…”
Section: The Effect Of Water Contamination On Hydrogen Permeationmentioning
confidence: 99%
“…The disk surfaces are artificially damaged (usually using a hardness indenter) and then run under lubricated slide/roll conditions [13,14,15,16,17]. Figure 12 shows a sequence of photographs for a dent initiating at a Rockwell indent run in oil [14]. The dents are first plastically flattened (in this case the yield stress of the steel is ~900MPa, significantly less than a bearing steel, so the plastic deformation is extensive), and then a crack initiates from the trailing edge.…”
Section: Twin Disk Simulationsmentioning
confidence: 99%